Herbal nanogels: Revolutionizing skin cancer therapy through nanotechnology and natural remedies - Sakshi Soni; Shivam K. Kori; Prashant Sahu; Varsha Kashaw; Rajiv Dahiya; Arun K. Iyer; Vandana Soni; Sushil K. Kashaw (Elsevier, 2024)
The escalating global incidence of skin cancer demands innovative therapeutic approaches that balance efficacy and reduced side effects. The convergence of nanotechnology and medicinal research has unveiled herbal nanogels as promising candidates for advancing skin cancer therapy. Skin cancer, comprising diverse malignancies, necessitates novel strategies to enhance treatment outcomes. Nanogels, intricate networks of cross-linked polymers at the nanoscale, have emerged as versatile vehicles for targeted drug delivery. Their ability to encapsulate a range of therapeutic agents and respond to stimuli offers a platform to revolutionize treatment paradigms. The taxonomy of nanogels encompasses physical cross-linked gels, liposome-modified nanogels, micellar nanogels, hybrid nanogels, and chemically cross-linked nanogels, each holding distinctive characteristics suitable for specific applications. The synthesis of nanogels is a precise craft involving techniques like photolithography, micro-moulding, and emulsion methods, enabling control over particle size, morphology, and drug-loading capacity. Stimuli-responsive nanogels present a dynamic facet of this field, exhibiting potential for targeted drug delivery. Noteworthy examples include LHRH-targeted nanogels and nanogels responsive to the intricate microenvironment of bacterial-accumulated tumors. One of the most intriguing developments lies in the fusion of herbal medicine and nanotechnology, paving the way for herbal nanogels. By incorporating bioactive plant-derived compounds into nanogel matrices, these constructs offer a holistic therapeutic approach. The convergence of nanotechnology and herbal medicine in the form of herbal nanogels presents a promising avenue for elevating skin cancer therapy. Through precise drug delivery mechanisms and responsiveness to complex microenvironments, nanogels exhibit a potential to reshape treatment norms. This comprehensive review provides an in-depth roadmap of the evolving landscape of herbal nanogels, illuminating their potential as effective, targeted, and minimally invasive tools for combating skin cancer.